PCR-based assays versus direct sequencing for evaluating the effect of KRAS status on anti-EGFR treatment response in colorectal cancer patients: a systematic review and meta-analysis. - Lianfeng Shan; Ming Li; Jianzhong Ma; Huidan Zhang (PLoS ONE)
Background The survival rate of colorectal cancer (CRC) patients carrying wild-type KRAS is significantly increased by combining anti-EGFR monoclonal antibody (mAb) with standard chemotherapy. However, conflicting data exist in both the wild-type KRAS and mutant KRAS groups, which strongly challenge CRC anti-EGFR treatment. Here we conducted a meta-analysis in an effort to provide more reliable information regarding anti-EGFR treatment in CRC patients. Methods We searched full reports of randomized clinical trials using Medline, the American Society of Clinical Oncology (ASCO), and the European Society for Medical Oncology (ESMO). Two investigators independently screened the published literature according to our inclusive and exclusive criteria and the relative data were extracted. We used Review Manager 5.2 software to analyze the data. Results The addition of anti-EGFR mAb to standard chemotherapy significantly improved both progression-free survival (PFS) and median overall survival (mOS) in the wild-type KRAS group; hazard ratios (HRs) for PFS and mOS were 0.70 [95% confidence interval (CI), 0.58-0.84] and 0.83 [95% CI, 0.75-0.91], respectively. In sub-analyses of the wild-type KRAS group, when PCR-based assays are employed, PFS and mOS notably increase: the HRs were 0.74 [95% CI, 0.62-0.88] and 0.87 [95% CI, 0.78-0.96], respectively. In sub-analyses of the mutant KRAS group, neither PCR-based assays nor direct sequencing enhance PFS or mOS. Conclusion Our data suggest that PCR-based assays with high sensitivity and specificity allow accurate identification of patients with wild-type KRAS and thus increase PFS and mOS. Furthermore, such assays liberate patients with mutant KRAS from unnecessary drug side effects, and provide them an opportunity to receive appropriate treatment. Thus, establishing a precise standard reference test will substantially optimize CRC-targeted therapies.